The ecological habitus of Indonesian student environmentalism. Issue 4 (2nd October 2017) - Nilan, Pam
ABSTRACT: This article considers the concept of ecological habitus in relation to pro-environmental discourses of Indonesian student activists. Further Bourdieusian concepts, cultural capital, illusio, doxa and hysteresis, throw interpretive light on how well-educated young Indonesians struggle in the field of environmental activism. It first outlines the concept of ecological habitus in relation to pro-environmental activism and then provides a discussion of environmental activism in Indonesia, before moving to consider environmental awareness in Indonesian universities. The methodology is briefly described before findings are presented under three key headings of expressed concern: global warming, forest loss and garbage.